2022
DOI: 10.1101/2022.01.30.478305
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Combating the SARS-CoV-2 Omicron variant with non-Omicron neutralizing antibodies

Abstract: The highly mutated and transmissible Omicron variant has provoked serious concerns over its decreased sensitivity to the current coronavirus disease 2019 (COVID-19) vaccines and evasion from most anti-severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) neutralizing antibodies (NAbs). In this study, we explored the possibility of combatting the Omicron variant by constructing bispecific antibodies based on non-Omicron NAbs. We engineered ten IgG-like bispecific antibodies with non-Omicron NAbs named GW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…As of February 22, 2022, 31 studies met the search criteria (Figure 1). Twelve of the studies were reported in a peer-reviewed publication [10][11][12][13][14][15][16][17][18][19][20][21]; 19 were published as preprints [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. Two additional studies comprised data available on the NIH National Center for Advancing Translational Sciences (NCATS) SARS-CoV-2 Variants and Therapeutics open data portal [41,42].…”
Section: Search Resultsmentioning
confidence: 99%
“…As of February 22, 2022, 31 studies met the search criteria (Figure 1). Twelve of the studies were reported in a peer-reviewed publication [10][11][12][13][14][15][16][17][18][19][20][21]; 19 were published as preprints [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. Two additional studies comprised data available on the NIH National Center for Advancing Translational Sciences (NCATS) SARS-CoV-2 Variants and Therapeutics open data portal [41,42].…”
Section: Search Resultsmentioning
confidence: 99%